(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article analyzes and studies the linguistic and linguopoetic properties of anthroponyms in Said Ahmad’s story “Qoplon”, the author’s individual skill in choosing names for the heroes of the work. The above story of the writer is taken as the research material, and the functional-semantic aspects of anthroponyms in this story are studied. The results of the research serve to enrich research in the field of literary text linguistics and onomastics.